Dis/Corporatization: The Biopolitics of Prosthetic Lives and Posthuman Trauma in Ghost in the Shell Films - Tong, Donna T. (Imaginations)

(untitled) (York University, 2019)
This paper explores the biopolitics both implicit and explicit in Mamoru Oshii’s film duology Ghost in the Shell. The prostheticization of life for Major Motoko Kusanagi is based upon an objectification of a cyborg self enabled and literalized through technology that is also a (mis)representation that conflates the biological self and technological self, and Oshii further problematizes this representation with the complication of the commodification and trafficking of posthuman lives, explicitly examined in more critical detail in the second film, Ghost in the Shell 2: Innocence. In other words, Oshii arguably imagines the extreme end of biopower in a posthuman world as human trafficking structured by a globalized political economy.